Integration Processes and Policies in Europe Contexts, Levels and Actors - Garcés-Mascareñas, Blanca; Penninx, Rinus (IMISCOE Research Series, 2016)
In this open access book, experts on integration processes, integration policies, transnationalism, and the migration and development framework provide an academic assessment of the 2011 European Agenda for the Integration of Third-Country Nationals, which calls for integration policies in the EU to involve not only immigrants and their society of settlement, but also actors in their country of origin. Moreover, a heuristic model is developed for the non-normative, analytical study of integration processes and policies based on conceptual, demographic, and historical accounts. The volume addresses three interconnected issues: What does research have to say on (the study of) integration processes in general and on the relevance of actors in origin countries in particular? What is the state of the art of the study of integration policies in Europe and the use of the concept of integration in policy formulation and practice? Does the proposal to include actors in origin countries as important players in integration policies find legitimation in empirical research? A few general conclusions are drawn. First, integration policies have developed at many levels of government: nationally, locally, regionally, and at the supra-national level of the EU. Second, a multitude of stakeholders has become involved in integration as policy designers and implementers. Finally, a logic of policymaking—and not an evidence-based scientific argument—can be said to underlie the European Commission’s redefinition of integration as a three-way process. This book will appeal to academics and policymakers at international, European, national, regional, and local levels. It will also be of interest to graduate and master-level students of political science, sociology, social anthropology, international relations, criminology, geography, and history. A great source for studying fundamental issues and policies of migrant integration in Europe. Professor Friedrich Heckmann, Director of European forum for migration studies, University of Bamberg F. Heckmann Historically grounded, thought-provoking in its conceptualisation of integration and ground breaking in its emphasis on the impact of countries of origin, exploring questions of vital importance to scholars and to policy makers from a local to European level. Sarah Spencer Director, Global Exchange on Migration and Diversity, COMPAS, Oxford. If you want a succinct, comprehensive, and insightful summary of scholarship on the politics of immigrant reception and the complex interplay between receiving countries, sending countries, and the E.U., written by the foremost scholars in the field, this is the volume for you. John Mollenkopf, Distinguished Professor of Political Science and Sociology, The Graduate Center, City University of New York.